Experimental Investigation of Operating Parameters in Power Generation by Lab-Scale Reverse Electro-Dialysis (RED) - Choi, Insoo; Han, Jun Young; Yoo, Sung Jong; Henkensmeier, Dirk; Kim, Jin Young; Lee, So Young; Han, Jonghee; Nam, Suk Woo; Kim, Hyoung-Juhn; Jang, Jong Hyun (대한화학회, 2016)
The reverse electro-dialysis (RED) is a renewable technology to produce electricity by mixing of differently concentrated water. In this study, the authors fabricated lab-scale RED, and attempted to evaluate the RED performance upon different operating parameters. Firstly, the effect of salinity ratio on the RED performance was examined by varying the concentration of low-salinity water. The performance was optimized by an increase in open circuit voltage (OCV) and cell resistance with salinity ratio. Individual resistances were analyzed by electrochemical impedance spectroscopy, and their impacts on power output were addressed. Second, the effect of flow rate of salinity solutions was studied, and it was found to affect the concentration polarization in RED. Lastly, the effect of the flow rate of electrode rinse solution was investigated, which increased the ionic shortcut current and decreased boundary layer resistance accordingly. Consequently, estimations on the trends in power output by changing operating parameters were made to determine the effective operation of RED.